A low cost ultra-wide-band inverted F-Antenna for Cognitive PMSE systems - Stöckle, Andreas; Brendel, Johannes; Rieß, Steffen; Rose, Richard; Fischer, Georg (International Conference on Wireless Information Technology and Systems, 2012)
elib2cris::1512001600,stoeckle2012
Keywords: UWB; IFA; self-complementary; UHF; ultra-wide-band; scanning antenna; SCA

A New Approach For A Dual-Polarized Low Cost Patch Antenna With Low Cross- Polarization, High Bandwidth And High Isolation - Stöckle, Andreas; Lutz, Steffen; Talai, Armin; Fischer, Georg (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2014)
In this paper a new approach for a dual- polarized broadband patch antenna is presented. A novel feeding approach enables a high -10dB band- width up to 21 % as well as an isolation more than -29 dB. The realized antenna gain is > 6 dBi in the frequency range of 1320 MHz to 1680 MHz. Addi- tional, due to the re ector shaping, a low back ra- diation is achieved. Since standard components and FR4 material are used, the antenna concept enables an e ective low cost antenna production.
elib2cris::1512001600,stoeckle2014

A Spectrum Sensing Network for Cognitive PMSE Systems - Brendel, Johannes; Rieß, Steffen; Stöckle, Andreas; Rummel, Rafael; Rose, Richard; Fischer, Georg (7th Workshop on Software Radios (WSR), 2012)
This paper is about a Spectrum Sensing Network (SSN) which generates an accurate radio environment map (e.g. power over frequency, time, and location) from a given application area. It is intended to be used in combination with cognitive Program Making and Special Events (PMSE) devices (e.g. wireless microphones). It consists of a distributed network of multiple scanning radio receivers and a central data management and storage unit. The parts of the SSN are presented in detail and the advantages and the use cases of such a sensing network structure are outlined.
elib2cris::1512001600,brendel2012

A Spectrum Sensing Network for Cognitive PMSE Systems - Brendel, Johannes; Rieß, Steffen; Stöckle, Andreas; Rummel, Rafael; Fischer, Georg (Frequenz, 2012)
This article is about a Spectrum Sensing Network (SSN) which generates an accurate radio environment map (e.g. power over frequency, time, and location) from a given application area. It is intended to be used in combination with cognitive Program Making and Special Events (PMSE) devices (e.g. wireless microphones) to improve their operation reliability. The SSN consists of a distributed network of multiple scanning radio receivers and a central data management and storage unit. The parts of the SSN are presented in detail and the advantages and use cases of such a sensing network structure will be outlined.
elib2cris::1512001600,brendel2012b
Keywords: PMSE; cognitive radio; spectrum sensing network; scanning receiver

Components and Implementation of a Spectrum Sensing Network for the UHF TV Band - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Rose, Richard; Fischer, Georg (European Microwave Conference (EuMC), 2013)
Spectrum sensing is a major part for the implementation of Cognitive Radio (CR) systems in order to enable dynamic access to the radio frequency spectrum. This paper is about a Spectrum Sensing Network (SSN) which generates an accurate radio environment map (i.e. power over frequency, time and location) in the UHF TV band from 470–870 MHz. It consists of a distributed network of multiple receivers with a broadband antenna and a central data management and storage unit. This contribution focuses on the implementation of such a scanning network which has been setup as universal research platform in several halls at the fairground in Berlin. The SSN itself is part of a complex CR system for Professional Wireless Microphone Systems (PWMS) that is able to provide a dynamic frequency allocation of the connected radio links.
elib2cris::1512001600,riess2013

Concept of an UHF Band Receiver for Spectrum Sensing Applications - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Rose, Richard; Fischer, Georg (IEEE International Symposium on Signals, Systems and Electronics, 2012)
Spectrum sensing is a major part for the implementation of Cognitive Radio (CR) systems in order to enable dynamic access to the radio frequency spectrum. This paper describes a concept for a scanning receiver in the UHF band from 470–870 MHz. Characteristics and design considerations of an Analog and Digital Front-End are given as well as the implementation of a Baseband Processor. This is the central module of the whole receiver and the interface to a higher-level controlling unit connected through a 100 Mbit/s Ethernet link. The control interface for the receiver is similar to a spectrum analyzer and therefore easy integrable in an already existing system. Special attention in the digital part is paid to an IF subsampling approach and the clock generation circuit for the ADC. For the sake of completeness the interface to a configurable antenna and some details to the realization of the power supply are also described. This concept has been implemented in hardware in order to enable investigations for the task of spectrum sensing. Our scanning receiver is part of a complex CR system for Professional Wireless Microphone Systems (PWMS) which should be able to provide a dynamic frequency allocation of the connected radio links.
elib2cris::1512001600,riess2012a

The Spectrum Sensing Network: Information Acquisition for the Cognitive PMSE System - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Schröter, Simon; Rose, Richard; Fischer, Georg (Shaker Verlag, 2014)
Accessing the frequency spectrum in a dynamic way has been discussed since several years. The Cognitive Radio (CR) technology was identi ed as enabler in order to use the spectral resources in a more e cient way. However, to guarantee interference free operation between multiple services, spectrum sensing plays a major role of designing such a system. This contribution focuses on the realization of the Spectrum Sensing Network (SSN) that has been developed during a research project in Germany. The SSN involves multiple sensor nodes consisting of a receiver with broadband antenna which are connected to a central controller that is in charge of handling the interfaces and acquired data of the SSN. With this setup it is possible to generate an accurate radio environment map, i.e. power over frequency, time and location, in the UHF frequency range from 470 to 870 MHz. After a short introduction to the system requirements and a project overview, attention is paid to the necessary components of such a distributed sensing grid. The measurement results and the discussion of possible advantages of a SSN show the added value for a CR system. Although, the application and demonstration was based on the improvement of operating conditions for Professional Wireless Microphone Systems (PWMS), the originated eld trial platform is open for reasearch activities related to other CR systems in this frequency range.
elib2cris::1512001600,riess2014
Keywords: PMSE; cognitive radio; spectrum sensing; sensing network; sensing grid; scanning controller; scanning receiver; scanning antenna; radio environment map; data fusion